1995
DOI: 10.1002/ajmg.1320600606
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of familial amyloidotic polyneuropathy (FAP)‐type I in Póvoa do Varzim and Vila do Conde (north of Portugal)

Abstract: Familial amyloidotic polyneuropathy (FAP-type I) was first described in Portugal by Andrade in 1952, a time when 54 among 64 patients (belonging to 25 families) originated from Póvoa do Varzim or its surrounding districts. Since then, a total of 1,233 patients, belonging to 489 pedigrees (so far unrelated), have been diagnosed at Centro de Estudos de Paramiloidose, Porto, Portugal. Although age-of-onset showed a wide range (17 to 78 years), 87% of these 1,233 patients developed symptoms before 40 years of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
149
2
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 17 publications
(6 reference statements)
13
149
2
3
Order By: Relevance
“…Among the 10 retained records, 8 records18, 21, 22, 23, 24, 25, 26, 27 directly reported 25 prevalence estimates pertaining to 11 countries (for pertinent details of the 10 retained records, see Table 1). National level prevalence estimates were reported for 10 of the countries, and these 10 constituted the core group of countries for which ATTR‐FAP population sizes were directly estimable.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 10 retained records, 8 records18, 21, 22, 23, 24, 25, 26, 27 directly reported 25 prevalence estimates pertaining to 11 countries (for pertinent details of the 10 retained records, see Table 1). National level prevalence estimates were reported for 10 of the countries, and these 10 constituted the core group of countries for which ATTR‐FAP population sizes were directly estimable.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6] Among Portuguese families, a remarkable wide variation in AO (19-82 years) has been observed, and an increasing number of late-onset cases (≥50 years) are being ascertained, including asymptomatic carriers aged 95 years. 4 Variation in AO between generations has also been observed: lateonset parents often have early-onset offspring (o40 years) -an evidence for anticipation -whereas the reverse has never been observed. Recently, our group has shown that anticipation is a true biological phenomenon in FAP ATTRV30M.…”
Section: Introductionmentioning
confidence: 99%
“…Val30Met (Met30) is almost the only variant found in Portugal, where mean age at onset is 33 years, a positive family history is frequent, and penetrance is high 7, 8, 9. In Japan, Met30 families with early onset neuropathy were initially identified in 2 limited areas (Arao district and Ogawa village) with a penetrance of 80% 10.…”
mentioning
confidence: 99%